1966
DOI: 10.1084/jem.123.5.881
|View full text |Cite
|
Sign up to set email alerts
|

Colicine K

Abstract: 1. The transfer of type K. colicinogeny to Shigella sonnei Phase II has been described. 2. The colicine elaborated by this microorganism is a lipopolysaccharide-protein complex which resembles the somatic antigen of the noncolicinogenic parent. 3. Although the colicine K of Escherichia coli K235 and of Sh. sonnei differ both chemically and serologically, they resemble each other in that both elicit type K colicine-neutralizing antibodies and both have the same bactericidal specificity. 4. The nature of the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1969
1969
1973
1973

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our early work (2) revealed that both colicins K (3) and V (4), obtained from the culture medium of the respective microorganisms, were invariably associated with the 0 antigen of the bacterium in question-an observation that was subsequently corroborated by others (5). We showed, furthermore, that when type K colicinogeny was transferred from a strain of Escherichia coli to an unrelated dysentery bacillus by mating, the bacteriocin and 0 antigen of the latter were inseparable (6). Despite this, we have always been alert to the possibility that the two might well be separate entities.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…Our early work (2) revealed that both colicins K (3) and V (4), obtained from the culture medium of the respective microorganisms, were invariably associated with the 0 antigen of the bacterium in question-an observation that was subsequently corroborated by others (5). We showed, furthermore, that when type K colicinogeny was transferred from a strain of Escherichia coli to an unrelated dysentery bacillus by mating, the bacteriocin and 0 antigen of the latter were inseparable (6). Despite this, we have always been alert to the possibility that the two might well be separate entities.…”
mentioning
confidence: 53%
“…When the colicin is recovered it has, in those instances thus far studied, proved to be associated with the lipopolysaccharide antigen of the bacillus in question (2)(3)(4)(5)(6). The use of the inducing agent mitomycin C, on the other hand, enhances the elaboration of the bacteriocin to such an extent that the latter can now actually be isolated as a free protein from the culture medium (9) or extracted from the bacterial cells themselves (9,13).…”
Section: Discussionmentioning
confidence: 99%
“…Sugar Content. Since colicin K contains the lipopolysaccharide of the somatic O antigen (Hinsdill and Goebel, 1966), colicins Ea-I and E3-II were examined for sugar content. Enzymatic determination of glucose after mild acid hydrolysis showed less than 0.1 mole of glucose/mole of colicin in each of these proteins.…”
Section: Resultsmentioning
confidence: 99%
“…If type K colicinogeny is transferred by mating to the unrelated organism Sh. sonnei (7), again it is the type-specific O antigen which bears the bacteriocin. Here too it was found that the neutralizing antibody elicited by the colicinogenic dysentery bacillus also failed to precipitate the homologous antigen.…”
Section: Discussionmentioning
confidence: 99%
“…We have suggested, therefore, that the inability of noninduced coticin to precipitate neutralizing antibody might be due to a steric hindrance of its antibody binding sites by the lipopolysaccharide component of the complex (7). In some measure this hypothesis is made more tenable by the fact that when Col K is dissociated with liquid phenol into its lipopolysaccharide and protein constituents, the colicin-rich protein is now capable of precipitating the neutralizing antibody (10).…”
Section: Discussionmentioning
confidence: 99%